The Effect of use of inventory management systems on availability of essential medicines and service delivery - a case study of Ishiara Level 4 Hospital - Waneno, N. S. (Strathmore University, 2024)
The study examined the effect of use of a digitized inventory management on availability of essential medicines and hence service delivery in a public hospital, Ishiara Level 4 Hospital in Embu County. The objectives of the study were to assess the current inventory management system, to evaluate the effect of staff skills and competence on inventory management and to forecast inventory management to aid in service delivery. This was done by use of primary data from questionnaires distributed to a sample size of 79 out of the 130 health workers directly involved in service provision at the facility. Secondary data was derived from the DHIS tool on trends of patient visits over a period of ten years to the dental clinic in the facility. The variables in the secondary data were the number of patients attended to and the number of procedures done. Analysis of the primary data was done using descriptive analysis and regression equation and analysis. Secondary data was analyzed using descriptive analysis using the excel tool, trend analysis, correlational analysis and predictive analysis by use of the ARIMAX and SARIMAX models. The main findings of the study were that inventory management system in the facility has not been able to ensure availability of essential medicines. Staff competence and skill affect inventory management use and hence service delivery. Therefore, there needs to be more facilitation of staff in terms of training and more emphasis needs to be put on training and facilitation of staff. From the secondary data, it was determined that predictive analysis can be useful in ensuring availability of essential medicines through improvement of inventory management. This would reduce cases of stock outs and patient referrals from the facility with an improvement in service delivery. Key terms; Inventory Management, Service delivery, Demand forecasting.
Full - text thesis